The immunological markers in patients infected with typhoid fever and rheumatoid arthritis, and bacteria sensitivity - M. I. Al-Wakeel; Z. N. Al-Laith; M. A. Khalaf; O. A. Mohsein (Regulatory Mechanisms in Biosystems, 2025)
Enteric fever and rheumatoid arthritis are common diseases that directly affect the human immune system. The aim of the study is determine the levels of inflammatory indicators in the two medical conditions and determine the extent of their impact on increasing the severity of the infection and its complications. This case-control study involved 100 patients with rheumatoid arthritis and typhoid fever, including 50 males and 50 females, along with 50 healthy controls (25 males and 25 females). The participants' average age ranged from 25 to 35 years. The study took place at Nasiriyah Teaching Hospital, Al-Haboubi Teaching Hospital, and Imam Hussein Teaching Hospital between 10/1/2023 and 20/3/2024. C-reactive protein (CRP), RF, anti-CCP, antinuclear antibody, IL-1α, IL-6, IL-33 and IL-36α levels were measured using enzyme-linked immunosorbent assay (ELISA). Bacteria were isolated and identified through molecular diagnostics, PCR, and culture methods. The results showed no significant differences in age and body mass index between the two groups. Ho w ever, there were significant changes in symptoms. CRP, RF, ANA, and Anti-CCP levels increased in the patient group, along with a rise in interleukin levels. 76 .0 % of cultures were positive, and PCR identified bacteria in 11.8% of cases. Drug sensitivity testing revealed that Ceftriaxone, Nitrofurantoin, and Ciprofloxacin were the most effective drugs, with a 100% success rate.